ANALISIS FRAMING ERICK THOHIR SEBAGAI KETUA UMUM PSSI DALAM PEMBERITAAN MEDIA REPUBLIKA ONLINE DAN KOMPAS.COM - Apta Nayottama, Fedora Reyvi; Gusti, Yutta Sihing (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
The election of Erick Thohir as General Chair of PSSI elicited various responses, both support and rejection from the public. This rejection was triggered because he was still the Minister of BUMN and was considered to have violated the rules on multiple positions. This study aims to determine the framing made by Republika Online and Kompas.com in reporting on Erick Thohir after the PSSI Congress on 16 February 2023, which inaugurated Erick Thohir as Chairman of PSSI for the 2023-2027 period. The research data comes from news reported by Republika Online and Kompas.com media for the period 16 February to 18 February 2023. The analysis uses the framing analysis method from Robert Entman which has 4 categorization elements, namely: Define problems, diagnose causes, and make moral judgments and treatment recommendations. The results of this study indicate that Republika Online has two news frames including Optimistic remarks from political figures for the election of Erick Thohir and the synergy between Erick and the National Police in forming the Anti Mafia Bola. Kompas.com has three news frames including Erick Thohir's promise after being elected, the issue of multiple positions that violate the rules, and the expectations of the coach figure.